A Comparison of Linguistic Obstacles to U.S. Immigration across Populations: Analysis of Oral Histories - Madeleine Albanese (Undergraduate Research Journal for the Human Sciences, 2016)
This paper explores the degree to which reports of linguistic difficulty for immigrants to the U.S. has changed over time. It analyzes the oral histories of European immigrants from the 1920s and South Asian immigrants from the 1970s. It is hypothesized that the degree of linguistic difficulty for immigrants to the U.S. would have lessened over time. Data from narratives of two waves of immigrants support the hypothesis. Reasons for this change in the degree of linguistic difficulty for immigrants to the U.S. are explored.
Keywords: Oral; Histories